Luzes... Câmera... Reflexão: Formação inicial de professores mediada por filmes - Mayrink, Mônica Ferreira (2007)
This study aims at describing and interpreting the phenomenon of the critical reflective teacher education mediated by films, from the point of view of those who lived this experience: the teacher-researcher and the students who joined the elective course A Escola no cinema: reflexão sobre a prática pedagógica a partir de filmes. The theoretical underpinnings for this study are: (a) a theory of teacher education emphasizing the importance of the development of their reflective capacity , based on the contributions of Dewey (1933; 1938/1967), Alarcão (1996a; 1996b;2003), Schön (1983, 1987, 1992a, 1992b), Freire (1979; 1980; 1982), Perrenoud (2002), Kemmis (1987), Zeichner (1993), Smyth (1992) and Pimenta (2002); (b) Vygotsky´s perspective of the sign as a mediator of the learning process (Vygotsky, 1930/1998;1934/1999); and (c) the understanding that the film constitutes a sign that may function as a mediator of the future teachers reflective development. Data were collected in the first semester of 2004, when thirteen Language and pedagogy students enrolled in the elective course mentioned above, in a university in São Paulo. This course was comprised of three distinct moments: in the first one, both the films and the topics for discussion were suggested by the teacherresearcher; in the second, the students suggested the topics they wanted to reflect upon and she selected the related films; and, in the third moment, the films and the discussion topics were chosen by the students. The study is based on the Hermeneutic-Phenomenological Approach and describes and interprets the phenomenon of the critical reflective teacher education mediated by films, using the thematization process proposed by van Manen (1990), and the systematization outlined by Freire (2006a). The results of the interpretations reveal that the structure of the phenomenon on focus was comprised by four major themes: Concepts which were associated with the theoretical repertoire developed in the course; Inquiries which were related to the dilemmas pointed out by students throughout the course (regarding the teachers and the students roles in the learning process; the inter-relations established among the different participants of the teaching and learning process; and the personal experiences in the knowledge construction about teaching); Searches for relationships between films and reality, films and theory, and films and students personal experience; and Changes that reveal the new perceptions that students start to have about films as well as about themselves, and new actions and knowledge that they believe they have developed during the reflective process shared together